2015
DOI: 10.1590/s0103-73312015000100012
|View full text |Cite
|
Sign up to set email alerts
|

Os significados da comorbidade para os pacientes vivendo com TB/HIV: repercussões no tratamento

Abstract: Resumo: O objetivo é compreender o processo de construção dos significados atribuídos pelos pacientes em relação à vivência da comorbidade tuberculose e HIV (TB/HIV), e sua repercussão nos respectivos tratamentos. Diante da complexidade do objeto, optou-se em estudá-lo à luz do referencial teórico do construcionismo social. O estudo qualitativo envolveu a realização de entrevista semiestruturada com dez pacientes com TB/HIV, acompanhados em um hospital na cidade do Rio de Janeiro. Os dados coletados foram subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0
17

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 5 publications
3
11
0
17
Order By: Relevance
“…Women believe that cultural beliefs through religion can help them overcome the barriers 293 imposed by the disease, by developing their will to live; the redefinition of personal relationships, 294 perception of the new meaning of life, and the reevaluation of the judgment on death minimize the 295 biopsychosocial repercussions of HIV infection [16,17]; also reinforce the findings of the current 296 research.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Women believe that cultural beliefs through religion can help them overcome the barriers 293 imposed by the disease, by developing their will to live; the redefinition of personal relationships, 294 perception of the new meaning of life, and the reevaluation of the judgment on death minimize the 295 biopsychosocial repercussions of HIV infection [16,17]; also reinforce the findings of the current 296 research.…”
supporting
confidence: 52%
“…The support given by family members, friends and partners guarantees a facilitating 315 condition to face the disease, and the family plays a fundamental role in the dimension of emotional 316 support and assistance in care during drug treatment [20,16,9].…”
mentioning
confidence: 99%
“…As for the variable "occupation" with the category "concerns about secrecy", it is observed that the condition of being away or retired, can give people psychological well-being, because they no longer have to return to work or are taken to seek new employment because of stress and confrontations related to disclosure of their HIV status to their employers and colleagues (15) ; and also the receipt of monthly salary in addition to providing the purchasing power of necessary goods, contributes to family expenses and provides more autonomy (6) . According to the practicing religion, the increase in QoL in the "general function" and "satisfaction with life" categories may be related to the role of religion as a source of support and hope in coping with problems (16) . However, the risk of disclosure of the diagnostic condition may reinforce HIV as a sin, increasing responsibility for the acts and guilt for infection (1,15) .Closing the remoteness of many people from religious participation, hindering the relationship with God, by feeling of revolt with the serological condition, because they believe that the disease is a divine punishment (4,17) .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13] These symptoms are frequent in a body that signals that something is organically in disarray, and it reveals the flourishing of feelings, sensations and emotions of a new reality: having and living with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%